Multiplex Serology for Measurement of IgG Antibodies Against Eleven Infectious Diseases in a National Serosurvey: Haiti 2014–2015 - Chan, YuYen; Martin, Diana; Mace, Kimberly E.; Jean, Samuel E.; Stresman, Gillian; Drakeley, Chris; Chang, Michelle A.; Lemoine, Jean F.; Udhayakumar, Venkatachalam; Lammie, Patrick J.; Priest, Jeffrey W.; Rogier, Eric William (Frontiers in Public Health, 2022)
Background: Integrated surveillance for multiple diseases can be an efficient use of resources and advantageous for national public health programs. Detection of IgG antibodies typically indicates previous exposure to a pathogen but can potentially also serve to assess active infection status. Serological multiplex bead assays have recently been developed to simultaneously evaluate exposure to multiple antigenic targets. Haiti is an island nation in the Caribbean region with multiple endemic infectious diseases, many of which have a paucity of data for population-level prevalence or exposure. Methods: A nationwide serosurvey occurred in Haiti from December 2014 to February 2015. Filter paper blood samples (n=4,438) were collected from participants in 117 locations and assayed for IgG antibodies on a multiplex bead assay containing 15 different antigens from 11 pathogens: Plasmodium falciparum, Toxoplasma gondii, lymphatic filariasis roundworms, Strongyloides stercoralis, chikungunya virus, dengue virus, Chlamydia trachomatis, Treponema pallidum, enterotoxigenic Escherichia coli, Entamoeba histolytica, and Cryptosporidium parvum. Results: Different proportions of the Haiti study population were IgG seropositive to the different targets, with antigens from T. gondii, C. parvum, dengue virus, chikungunya virus, and C. trachomatis showing the highest rates of seroprevalence. Antibody responses to T. pallidum and lymphatic filariasis were the lowest, with less than 5% of all samples IgG seropositive to antigens from these pathogens. Clear trends of increasing seropositivity and IgG levels with age were seen for all antigens except those from chikungunya virus and E. histolytica. Parametric models were able to estimate the rate of seroconversion and IgG acquisition per year for residents of Haiti. Conclusions: Multiplex serological assays can provide a wealth of information about population exposure to different infectious diseases. This current Haitian study included IgG targets for arboviral, parasitic, and bacterial infectious diseases representing multiple different modes of host transmission. Some of these infectious diseases had a paucity or complete absence of published serological studies in Haiti. Clear trends of disease burden with respect to age and location in Haiti can be used by national programs and partners for follow-up studies, resource allocation, and intervention planning.